Gender Sensitivity among selected students of University of the Philippines Visayas Tacloban College (UPVTC) and the Eastern Visayas State University (EVSU), SY 2008-2009 A preliminary assessment. - Catilogo, Konnie Reika R.; Yanos, Jonnalyn Fil C. (Tacloban City Konnie Reika R. Catilogo, 2009)
This study is entitled "Gender Sensitivity Among Selected Students of the University of the Philippines Visayas Tacloban College (UPVTC) and the Eastern Visayas State University (EVSU), SY 2008-2009 A Preliminary Assessment." This specifically seeks to answer the following questions: 1.) Is there a difference in the level of gender sensitivity between students (UPVTC) who had taken gender sensitive courses from those students (EVSU) who have not? and 2.) Who is more gender sensitive? Is it the male or the female respondents? Is there a difference in the level of gender sensitivity of the male and female? The researchers hypothesized that: Ho:X1 = X2 or there is no significant difference on the level of gender sensitivity between both schools whether they took gender sensitivity courses on the past; H1: X1 not equal to X2 or there is a significant difference on the level of gender sensitivity of the students from both schools; and H0:Xm = Xf or there is no significant difference on the level of gender sensitivity between male and female H1:Xm is not equal to Xf or there is a significant difference on the level of gender sensitivity between male and female.
It is essential to determine whether gender courses play a significant role in molding every student's mind vis-a-vis gender biases and perception of inequalities in the roles assigned to men and women. This study was conducted in the University of the Philippines Visayas Tacloban College (UPVTC) and Eastern Visayas State University (EVSU), Tacloban City. The researchers utilized a purposive way of sampling. Eastern Visayas State University, a public school, is composed of 9,275 students. The respondents from EVSU were 100 junior and senior students from the College of Business and Entrepreneurship. Whereas, the University of the Philippines Visayas Tacloban College, a public school too, is comprised of 1,067 students. The respondents from UPVTC were 100 junior and senior students from the Division of Management. Majority of the respondents were female. They composed 78% or 156 of the total population. For the data gathering, a gender survey questionnaire was administered to each of the respondents. The researchers made used of the two-tailed T-test method in computing for the variables.
Based on the gathered research data, the researchers therefore conclude that: 1) There is a significant difference on the level of gender sensitivity between the students of the two schools. The researchers presumed that other factors may have influenced their awareness on gender sensitivity. One possible factor is that most of UPVTC students have taken gender courses in the past. Another is the fact that 78% of the population was women, which are deemed to be more sensitive to gender equality. And similarly, the locale of research was in the urban setting where people are more open-minded and liberal in nature; 2.) Therefore, the lack of gender courses in schools may be a basis in judging the gender sensitivity or awareness of the students; 3.) And thus Ho is rejected and H1 is accepted.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science